The Effect of Entrepreneurship Leadership on Business Performance Mediated by Competitive Advantage and Dynamic Capability in Batik Giriloyo MSMEs - Rokhanawati, Deden Rokhanawati; Sabihaini; R. Heru Kristanto (West Science Journal Economic and Entrepreneurship, 2024)
This study examines and analyses the effect of entrepreneurship leadership on the business performance of Giriloyo Batik MSMEs by involving the mediating variables of competitive advantage and dynamic capability. The research method uses a quantitative approach with a sample of 80 respondents. The analysis tool uses PLS. The research findings show that entrepreneurship leadership positively affects business performance, which has yet to be accepted. In contrast, entrepreneurship leadership positively and significantly impacts competitive advantage and dynamic capability is accepted. Competitive advantage that has a positive effect on business performance is not taken; dynamic capability has no effect and is not significant to business performance. While the indirect effect test results show that entrepreneurship leadership impacts business performance mediated by competitive advantage, it is not supported; entrepreneurship leadership's effect on business performance mediated by dynamic capability is also not supported, which means that the direct and indirect effects are insignificant. In other words, entrepreneurship leadership's effect on business performance mediated by competitive advantage is not supported, and entrepreneurship leadership's effect on business performance mediated by dynamic capability is also not supported. In other words, competitive advantage and dynamic capability have yet to be able to mediate the relationship between entrepreneurship leadership and business performance at this time. This is a future challenge for Giriloyo Batik MSMEs.